2019
DOI: 10.1029/2019gb006256
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Plankton Community Structure on Sinking Velocity and Remineralization Rate of Marine Aggregates

Abstract: Gravitational sinking of photosynthetically fixed particulate organic carbon (POC) constitutes a key component of the biological carbon pump. The fraction of POC leaving the surface ocean depends on POC sinking velocity (SV) and remineralization rate (Cremin), both of which depend on plankton community structure. However, the key drivers in plankton communities controlling SV and Cremin are poorly constrained. In fall 2014, we conducted a 6‐week mesocosm experiment in the subtropical NE Atlantic Ocean to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 139 publications
6
83
2
Order By: Relevance
“…On the other hand, although free‐living assemblages were shown to be much less vertically connected than particle‐attached assemblages (Mestre et al., 2018), our results indicate that they still retain a certain surface imprint, with the abundances of surface picocyanobacteria emerging as the strongest predictors of free‐living bathypelagic communities. Variations in picocyanobacteria can also be indicators of varying carbon export rates, given that small primary producers enable the formation of dense aggregates that can sink efficiently (Bach et al., 2019; Guidi et al., 2016; Richardson & Jackson, 2007). Thus, a possibility is that a fraction of the attached communities arriving via sinking particles detaches and appears in the free‐living realm (Mestre et al., 2018), explaining the signature of surface conditions on free‐living taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although free‐living assemblages were shown to be much less vertically connected than particle‐attached assemblages (Mestre et al., 2018), our results indicate that they still retain a certain surface imprint, with the abundances of surface picocyanobacteria emerging as the strongest predictors of free‐living bathypelagic communities. Variations in picocyanobacteria can also be indicators of varying carbon export rates, given that small primary producers enable the formation of dense aggregates that can sink efficiently (Bach et al., 2019; Guidi et al., 2016; Richardson & Jackson, 2007). Thus, a possibility is that a fraction of the attached communities arriving via sinking particles detaches and appears in the free‐living realm (Mestre et al., 2018), explaining the signature of surface conditions on free‐living taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The amount, quality, size and sinking rates of the particles leaving the photic ocean are ultimately determined by the community structure of phytoplankton and other food web processes such as grazing (Bach et al., 2019; Boyd & Newton, 1995; Guidi et al., 2009; Laurenceau‐Cornec, Trull, Davies, De la Rocha, & Blain, 2015; Stukel, Landry, Benitez‐Nelson, & Goericke, 2011). For example, diatoms and mesozooplankton are considered main drivers of carbon export due to fast sinking rates of large cells or dense faecal pellets, respectively (Agustí et al., 2015; Al‐Mutairi & Landry, 2001; Boyd & Newton, 1995; Fender et al., 2019; Stukel et al., 2011), but multiple studies have unveiled that groups such as picoeukaryotes, radiolarians, ciliates, dinoflagellates and even picocyanobacteria can also be delivered at depth, probably as fast‐sinking aggregates (Agustí et al., 2015; Amacher, Anderson, & Massana, 2009; Boeuf et al., 2019; Fontánez, Eppley, Samo, Karl, & DeLong, 2015; Guidi et al., 2016; Gutiérrez‐Rodríguez et al., 2019; Lundgreen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The often-stated goal of studies into BCP efficiencies is to resolve the mechanisms that control the transfer of OM to depth (37). No single mechanism has been found to control BCP efficiencies, although considerable effort has focused on the potential relationships between POC flux and NPP (38,39), food web controls (40,41), ballast (42,43), oxygen (44,45), temperature (46)(47)(48), and variable sinking and degradation rates (49)(50)(51). However, if we want to quantify the mechanism(s) that lead to differences in the BCP efficiencies, we need to start by normalizing POC flux to the depth where it is produced and below which only particle flux attenuation occurs.…”
Section: Why Does An Ez-based Reference Depth Matter?mentioning
confidence: 99%
“…In a recent study investigating copepod grazing behavior on aggregated particles, Koski et al (2017) demonstrated that both harpacticoida and poecilostomatoida copepods were able to feed on aggregates and could thus attenuate the particle carbon flux. Aggregation processes and dynamics are increasingly understood via the combination of laboratory experiments and models (Beauvais et al, 2006;Passow and De La Rocha, 2006;Gärdes et al, 2011;Jackson, 2015;Prairie et al, 2019), mesocosm experiments (Alldredge et al, 1995;Passow and Alldredge, 1995b;Svensen et al, 2001Svensen et al, , 2002Moriceau et al, 2018;Cisternas-Novoa et al, 2019), and in situ observations (Lampitt et al, 2010;Laurenceau-Cornec et al, 2015;Nowald et al, 2015;Giering et al, 2017;Cavan et al, 2018;Bach et al, 2019). In the meantime, studies focusing on disaggregation processes due to remineralization or zooplankton activity (Goldthwait et al, 2004;Taucher et al, 2018) remain limited despite their importance in providing new insights to better understand particle export in the mesopelagic zone.…”
Section: Introductionmentioning
confidence: 99%
“…They may also enhance carbon export by (1) egesting large sinking fecal pellets (Turner, 2015;Lalande et al, 2016;Steinberg and Landry, 2017), (2) boosting the aggregation, as seen for cyanobacteria, appendicularians, and doliolids (Moriceau et al, 2018;Taucher et al, 2018), and (3) increasing the particle sinking rates when increasing the silicon content of diatoms (Pondaven et al, 2007). Swimming activity being intrinsically linked to feeding, copepod flexible diet may also modulate particle fluxes through differential grazing between free diatoms and aggregated diatoms (Bochdansky and Herndl, 1992;Bochdansky et al, 1995) or by changing the composition of the phytoplankton community (Bach et al, 2019). Their distinct functional feeding traits as filter feeders or ambush feeders (Kiørboe, 2011;Lombard et al, 2013b;Koski et al, 2017) make them organisms of particular interest to study particle dynamics.…”
Section: Introductionmentioning
confidence: 99%